Novel Fluticasone Propionate and Salmeterol Fixed-Dose Combination Nano-Encapsulated Particles Using Polyamide Based on L-Lysine - Mohammad H. Alyami; Eman Zmaily Dahmash; Dalia Khalil Ali; Hamad S. Alyami; Hussien AbdulKarim; Samar A. Alsudir (MDPI AG, 2022)
One of the key challenges in developing a dry powder inhaler (DPI) of an inhalable potent fixed-dose combination (FDC) is the ability of the formulation to generate an effective and reproducible aerosol able to reach the lower parts of the lungs. Herein, a one-step approach is presented to expedite the synthesis of nanoaggregates made from a biocompatible and biodegradable polyamide based on L-lysine amino acid employing market-leading active pharmaceutical ingredients (fluticasone propionate (FP) and salmeterol xinafoate (SAL)) for the management of asthma. The nanoaggregates were synthesized using interfacial polycondensation that produced nanocapsules with an average particle size of 226.7 ± 35.3 nm and zeta potential of −30.6 ± 4.2 mV. Differential scanning calorimetric analysis and x-ray diffraction, as well as scanning electron microscopy of the produced FDC, revealed the ability of the produced nanocapsules to encapsulate the two actives and display the best aerodynamic performance. The FDC nanocapsules displayed 88.5% and 98.5% of the emitted dose for FP and SAL, respectively. The fine particle fraction of the nominated dose was superior to the marketed product (Seretide Diskus®, Brentford, United Kingdom). The in-vitro release study showed an extended drug release profile. Our findings suggest that nanoaggregates using polyamides based on L-lysine and interfacial polycondensation can serve as a good platform for pulmonary drug delivery of FDC systems.